2015
DOI: 10.2196/mental.4133
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Health Behavior Theory and Design Elements in Serious Games

Abstract: BackgroundInternet interventions for improving health and well-being have the potential to reach many people and fill gaps in service provision. Serious gaming interfaces provide opportunities to optimize user adherence and impact. Health interventions based in theory and evidence and tailored to psychological constructs have been found to be more effective to promote behavior change. Defining the design elements which engage users and help them to meet their goals can contribute to better informed serious gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 51 publications
1
63
0
1
Order By: Relevance
“…This aspect was also highlighted and praised by sexual minority youth, who felt that allowing them to personalise the avatar's gender and appearance reflected their real‐world experience of challenging gender expectations (Lucassen et al., ). Furthermore, the research team have analysed qualitative data from five studies of SPARX to understand how users’ perceptions and elements of the intervention map onto the autonomy, competence and relatedness aspects of self‐determination theory, which in turn have been theorised as key factors influencing engagement and adherence to computerised interventions (Cheek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This aspect was also highlighted and praised by sexual minority youth, who felt that allowing them to personalise the avatar's gender and appearance reflected their real‐world experience of challenging gender expectations (Lucassen et al., ). Furthermore, the research team have analysed qualitative data from five studies of SPARX to understand how users’ perceptions and elements of the intervention map onto the autonomy, competence and relatedness aspects of self‐determination theory, which in turn have been theorised as key factors influencing engagement and adherence to computerised interventions (Cheek et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cheek and colleagues (75), for example, integrated Self-Determination Theory with Gaming Theory to design an online depression treatment intervention for adolescents in Australia. Inclusion of these details may help researchers identify which technological components have greater success than others when working with youth across different settings (76).…”
Section: Discussion: Emergent Issues In the Fieldmentioning
confidence: 99%
“…Besides the desire for the tool to be effective in improving wellbeing levels, young people reported that overall they would ideally like the tool to feature flexibility in choice and function [T7]. This finding is not surprising given the modern standards of current technology more generally, that provide fruitful ground for the implementation of variable and customisable tools to suit the modern consumer's needs [73,74]. When considering that contemporary digital health interventions, such as E-health, are characterised by their ability to increase the effectiveness of and adherence to therapy, the clinical implications of the incorporation of flexible features in self-management tools can be of paramount importance.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%